RELEVANSI WACANA PERSUASIF IKLAN HANDBODY DALAM PEMBELAJARAN BAHASA INDONESIA: Wacana Persuasif Pada Iklan Handybody - Putri Ramadhani; Lisa Septia Dewi Br. Ginting (Universitas Asahan, 2025)
This study analyzes the persuasive discourse strategies employed in handbody product advertisements and identifies their relevance within the context of Indonesian language learning. As a form of mass communication, advertisements are inherently designed to influence audiences to take specific actions. In handbody advertisements, language is often manipulated to construct an ideal image and emphasize product benefits to attract consumer attention. The method used in this study is descriptive qualitative with a literature review approach. Data were collected through an in-depth analysis of various handbody advertisements from print and digital media, as well as literature related to persuasive discourse theory and Indonesian language education. The data were analyzed inductively to identify patterns of persuasive language, including word choice, sentence structure, language style, and rhetorical strategies. The findings reveal that advertisements utilize a variety of techniques to appeal to both emotional and rational aspects of the audience. The implication of this study is that persuasive discourse analysis can be integrated into Indonesian language instruction to enhance students’ critical thinking skills in understanding and producing persuasive texts.